Inhibition of miRNA associated with a disease-specific signature and secreted via extracellular vesicles of systemic lupus erythematosus patients suppresses target organ inflammation in a humanized mouse model - Young, Nicholas A.; Schwarz, Emily; Zeno, Braden M.; Bruckner, Shane; Mesa, Rosana A.; Jablonski, Kyle; Wu, Lai-Chu; Roberson, Elisha D. O.; Jarjour, Wael N. (Frontiers in Immunology, 2024)
Distinct, disease-associated intracellular miRNA (miR) expression profiles have been observed in peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematous (SLE) patients. Additionally, we have identified novel estrogenic responses in PBMCs from SLE patients and demonstrated that estrogen upregulates toll-like receptor (TLR)7 and TLR8 expression. TLR7 and TLR8 bind viral-derived single-stranded RNA to stimulate innate inflammatory responses, but recent studies have shown that miR-21, mir-29a, and miR-29b can also bind and activate these receptors when packaged and secreted in extracellular vesicles (EVs). The objective of this study was to evaluate the association of EV-encapsulated small RNA species in SLE and examine the therapeutic approach of miR inhibition in humanized mice. Plasma-derived EVs were isolated from SLE patients and quantified. RNA was then isolated and bulk RNA-sequencing reads were analyzed. Also, PBMCs from active SLE patients were injected into immunodeficient mice to produce chimeras. Prior to transfer, the PBMCs were incubated with liposomal EVs containing locked nucleic acid (LNA) antagonists to miR-21, mir-29a, and miR-29b. After three weeks, blood was collected for both immunophenotyping and cytokine analysis; tissue was harvested for histopathological examination. EVs were significantly increased in the plasma of SLE patients and differentially expressed EV-derived small RNA profiles were detected compared to healthy controls, including miR-21, mir-29a, and miR-29b. LNA antagonists significantly reduced proinflammatory cytokines and histopathological infiltrates in the small intestine, liver, and kidney, as demonstrated by H&E-stained tissue sections and immunohistochemistry measuring human CD3. These data demonstrate distinct EV-derived small RNA signatures representing SLE-associated biomarkers. Moreover, targeting upregulated EV-encapsulated miR signaling by antagonizing miRs that may bind to TLR7 and TLR8 reveals a novel therapeutic opportunity to suppress autoimmune-mediated inflammation and pathogenesis in SLE.